Driving Force and Logic of Development of Advanced High Strength Steels for Automotive Applications. Issue 10 (11th June 2013) - Bouaziz, Olivier; Zurob, Hatem; Huang, Mingxin
Abstract: The major scientific and technological advances and breakthroughs of advanced high strength steels (AHSS) were achieved due to the strong demands of automotive industry. The development of AHSS began in the early 1980s with the aim of improving passenger safety and weight‐saving. The present paper presents the driving forces and logic of development of various AHSS for automotive applications since 1980s. The importance of crash performance, weight‐saving, formability, and rigidity are critically reviewed for the development of new steel grades for automotive applications. The logical sequences of the development of dual phase (DP) steel, transformation induced plasticity (TRIP) steels, tempered DP steels, complex phases (CP) steels, Ferrite‐Bainite steels, hot‐stamping technology, twinning induced plasticity (TWIP) steels, Quench and Partitioning (Q&P) steels, Medium Mn steels, and steels–polymer composites are presented. Abstract : The development of Advanced High Strength Steels (AHSS) began with the aim of improving passenger safety and weight‐saving. The image shows the automative parts (in red) that are made of AHSS.